2004
DOI: 10.1002/elps.200406061
|View full text |Cite
|
Sign up to set email alerts
|

Performance of electrokinetic supercharging for high‐sensitivity detection of DNA fragments in chip gel electrophoresis

Abstract: Chip gel electrophoresis was explored for high-sensitivity detection of DNA by combining electrokinetic injection with transient isotachophoresis preconcentration (here named electrokinetic supercharging (EKS)). Low concentrations (0.2 mg/L) of DNA sample could be detected without fluorescence labeling using a conventional UV detector (at 260 nm). On a single-channel microchip, identification of PCR product was performed by exploiting both external and internal calibration methods. The deviation between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 23 publications
(22 reference statements)
0
33
0
Order By: Relevance
“…For example Quirino and Terabe [20] have demonstrated that SEFs as high as several hundreds of thousands are reachable if FESI is used under sweeping condition. Also, Hirokawa and co-workers [21][22][23] have introduced few years ago the electrokinetic supercharging (EKS) methodology. In EKS, analytes are introduced into the separation capillary with an electrokinetic injection under conditions that are suitable for isotachophoretic stacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example Quirino and Terabe [20] have demonstrated that SEFs as high as several hundreds of thousands are reachable if FESI is used under sweeping condition. Also, Hirokawa and co-workers [21][22][23] have introduced few years ago the electrokinetic supercharging (EKS) methodology. In EKS, analytes are introduced into the separation capillary with an electrokinetic injection under conditions that are suitable for isotachophoretic stacking.…”
Section: Introductionmentioning
confidence: 99%
“…In EKS, analytes are introduced into the separation capillary with an electrokinetic injection under conditions that are suitable for isotachophoretic stacking. So far, EKS has been applied to rare-earth chlorides [21], DNA fragments [23], and proteins denaturated by SDS [22].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of these two fields requires researchers knowledgeable in both subjects, but many scientists lack such a comprehensive background. The relatively low sensitivity of CE analysis is the second limitation in the field of DNA analysis [136][137][138][139][140]. The double bond formed by the base group in DNA has a low UV-visible absorption, and a normal UV detector has a low sensitivity.…”
Section: Limitations Advantages and Future Development Of Ce Based Omentioning
confidence: 99%
“…The instrument was utilized in testing the applicability of transforming affinity CE (ACE) techniques to microchip format [50], in the rapid separation of antimicrobial metabolites with high efficiency [51], and in chiral separations of pharmaceuticals by CD EKC [52,53]. The same system was employed in developing a method to test for nitrogen monoxide metabolites in biological fluids [54], along with a single-step quantitation of DNA [55], and chip gel electrophoresis method for high-sensitivity DNA detection [56], as well as a monosaccharide derivative separation [57].…”
Section: Absorbance Detectionmentioning
confidence: 99%